2012
DOI: 10.1021/jp306873v
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin Unfolding in Crowding and Confinement

Abstract: Crowding and confinement have often been used synonymously with regard to their effect on the structure and dynamics of proteins. In this work, we have investigated the unfolding of the protein myoglobin (Mb) entrapped in the confinement of the water pool of AOT reverse micelles and in the presence of some commonly used macromolecular crowding agents (Ficoll 70, Dextran 70, and Dextran 40). Our results reveal that confinement effects can be quite destabilizing in nature for Mb with the extent of distortion dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 63 publications
3
49
0
Order By: Relevance
“…In presence of SiO 2 NP, CAT undergoes a distortion in its secondary structure as observed from the obvious decrease in the intensity of its helical band at 208 nm and 220 nm. The above result was in agreement with the UV-vis studies [26].…”
Section: Spectrasupporting
confidence: 92%
“…In presence of SiO 2 NP, CAT undergoes a distortion in its secondary structure as observed from the obvious decrease in the intensity of its helical band at 208 nm and 220 nm. The above result was in agreement with the UV-vis studies [26].…”
Section: Spectrasupporting
confidence: 92%
“…Dextran 70 has been demonstrated to decrease the stability of rPrP C (properly folded prion protein) by 8°C and rPrP 80R by 12.5°C [40]. Similar to Dextran 70, Ficoll 70 was also shown to enhance unfolding of myoglobin by urea [29]. Furthermore, in a recent development by our laboratory [41], holo α-lactalbumin was observed to be destabilized by several degrees (in terms of T m , melting temperature) in the presence of polymer crowders due to reduction in its calcium-binding affinity.…”
Section: Macromolecular Crowding Destabilizes Macromolecules and Incrmentioning
confidence: 94%
“…All these opposing effects are described as "hostile or negative effect" in the entire manuscript. For instance, macromolecular crowding has been demonstrated to have a destabilizing influence on the stability of Myoglobin [29]. Recent investigations made by Fan et al suggested a decrease in the activity of recombinant human brain-type creatine kinase under crowded conditions [30].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been carried out to investigate the various underlying mechanisms and driving forces that are important for proteins, having different degrees of structural complexity, to fold in a physiologically relevant timescale. [6][7][8] Irrespective of whether one uses dilute buffer solutions or the crowded media, most of the folding studies have focused on either single domain proteins 9 or those that are a part of bigger proteins having multiple domains 10,11 or involving DNA. These macromolecules, popularly termed crowding agents, through their excluded volume effect, reduce the space available for the biological molecule of interest.…”
Section: Introductionmentioning
confidence: 99%